Avanços na produção e formulação de inoculantes microbianos visando uma agricultura mais sustentável. - FLORENCIO, C. (2022)
ADVANCES IN THE PRODUCTION AND FORMULATION OF MICROBIAL INOCULANTS FOR A MORE SUSTAINABLE AGRICULTURE. The wide application of beneficial microorganisms in agriculture as inoculants to combat pests and diseases and/or to improve soil fertility and the nutrients availability for plants has been considered as an effective and more sustainable alternative than chemical fertilizers and agricultural defensives. However, it is necessary to examine all processing steps of these bio-based products under a more integrated view including the type of microorganisms and the whole production process in order to reduce dependence on synthetic chemical inputs. Here, recent developments on the production and formulation technologies of microbial inoculants and the main types of inoculants currently applied in agriculture are addressed. The different types of microbial formulations are compared with emphasis on the encapsulation technology. Moreover, the application of biofertilizers in seed coating and a new approach to apply biocomposites as fertilizers are discussed, presenting the main challenges and future perspectives to promote more sustainable agriculture practices.